Pelatihan Menyusun Proposal Skripsi untuk Mahasiswa Sarjana - Baidowi, Ach. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2024)
Thesis writing remains one of the most feared tasks among students, with many lacking an understanding of how to produce a well-structured thesis. This training was conducted to provide students with a comprehensive understanding of how to quickly and effectively compose a high-quality thesis. The training employed a PAR (Problem-Action-Result) approach using Zoom meetings, laptops, and educational materials. Training outcomes include: creating a good title involves selecting a relevant and innovative topic, identifying the problem, and crafting a title that reflects both the topic and research methodology. The background section should explain the relevance of the topic, problem context, and literature review to identify research gaps. Research focus should include understanding variables, choosing relevant theories, and determining supporting variables. The literature review involves understanding variables X and Y, research location, and both main and supporting theories. Finally, the research methodology must describe the type and approach of the research, data collection and processing techniques, data validity, and hypothesis testing for quantitative research